The Relationship between Religious Attitude, Psychological Resilience and Depression: A Quantitative Research on Syrian Adolescent Individuals - Cengiz, Erhan; Sagir, Zeynep (Ataturk Univ, 2023)
This study aims to determine the relationship between religious attitudes, psychological resilience and depression in Syrian adolescent individuals. The sample of the study consists of 216 Syrian individuals aged 13-18 residing in Elazig. The average age is 15,31. About 124 of the participants were female, and 92 were male. Personal Information Form, Beck Depression Inventory II, Religious Attitude Scale, and Child and Adolescent Resilience Scale were used to collect data. The data were analyzed using the Statistical Package for Social Sciences Statistics software, version 22.0. In the study, the following results were obtained regarding the Syrian sample: there is a negative and significant relationship between depression and religious attitude levels; there is a negative and significant relationship between depression and psychological resilience levels; and there is a positive and significant relationship between psychological resilience and religious attitude levels. In addition, the research findings showed that resilience and religious attitudes explained approximately 20% of the total variance in the level of depression in Syrian adolescents.
Keywords: Psychology of Religion; Religious Attitude; Adolescence; Depression; Psychological Resilience